Impactos socioculturales generados por el turismo en la parroquia Vilcabamba, cantón Loja. - Sarango Sarango., Karen Daniela (2023)
The Vilcabamba Valley is characterized by being a long-lived place and for some years its socio-cultural environment has been changing with the arrival of new migratory processes settled in the town, which have causal a substation changes in the parish with the introduction of new customs and traditions that have influenced the locality-society and culture have been affected by the various changes described above. In this way, the changes brought about in the parish are identified and evaluated with the study of the following research proposal: “sociocultural impacts generated by tourism in the Vilcabamba parish, Loja canton”. This is how three research questions are arise that address the problem from three objectives that analyze each context: Identify the sociocultural impacts generated by tourism in the parish of Vilcabamba, crate a methodology to assess the sociocultural impacts generated by tourism and carry out a tourism reinforcement proposal. In order to meet the objectives of the research, the bibliographic review was offered as a research method together whit a focus group with the Department Of Tourist Information in which negative and positive impacts were identified as the contribution to the economic life of the population, the introduction of new gastronomy, as well as clothing and foreign language, in addition a methodology for the evaluation of sociocultural impacts is proposed with the results of the first objective in which on adaption of the Acceptable change Limits Methodology for sociocultural impacts is carried out together with the Likert Scale that measures the level of impact. The results of the evaluation allow to strengthen a proposal with the actors of the parish in which three objectives are proposed in order to train the providers of tourist services, create programs that rescue the dances and traditions of the town, in addition to promoting the creation of contingency plans reduce the sociocultural impacts in the Vilcabamba parish.